RESTORATION AND RECONSTRUCTION OF BUILDING AND STRUCTURES IN KRASNODAR, RUSSIAN FEDERATION: A DEEP DIVE INTO MODERNIZATION AND URBAN RENEWAL - Simanjuntak, Raja Agung Hasudungan; Darwis, Mardis; Rambak, Ezra Pasereng; Rahman, La; Wardani, Ayu; Aji, Angga Asteriasti (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
This article explores the complex landscape of building reconstruction in Krasnodar, Russia, a city experiencing rapid urban development [3][6]. It examines the drivers behind reconstruction projects, focusing on the need to address both objective and subjective obsolescence in civil and industrial buildings. The machine-building complex of the Krasnodar region includes enterprises of oil and gas, railway, agricultural and food engineering. The study highlights the multifaceted goals of modern reconstruction, including enhancing living comfort, increasing residential capacity, and improving the urban environment[3]. It also delves into the challenges faced during urban reconstruction, such as managing increased loads on foundations, working within confined construction sites, and modernizing existing utilities. The article further examines the diverse repair strategies employed, emphasizing the importance of tailoring methods to specific building materials, damage extent, and site conditions. Ultimately, it underscores the need for a holistic and integrated approach to reconstruction, balancing progress and preservation to create sustainable, resilient, and aesthetically pleasing urban spaces that enhance the quality of life for Krasnodar's residents[3][4].